LISST: IT Supported Language Teaching and Learning - Grucza, Sambor; Szerszeń, Paweł (Glottodidactica, 2014)
The Internet didactic modules for the purposes of teaching languages and translation have been marked by a low degree of interactivity so far. Tests have been proofed and assessed automatically by an operating system, solely according to the answers entered to the system beforehand. Unlike the previous systems, the aim of the preparation of the Linguistically Smart Software System for Glottodidactics and Translation Didactics is to enable an automatic assessment of all full sentences written by the students themselves. The main goal of the text is to describe a new linguistically smart software, which was developed for Polish and German universities on a largescale in order to teach a given language and translation effectively.